Lean manufacturing practices in textile industries – a case study. (1st March 2013) - Saleeshya, P.G.; Raghuram, P.; Vamsi, N.
Lean manufacturing is a philosophy of eliminating waste through continuous improvement. This paper is an outcome of a case study conducted in a textile industry in south India. Though the concept of lean manufacturing has shown good results in continuous process industry, it has not been extensively used as compared to discrete manufacturing industries. Process industries, especially textile industries, have automatic machinery which are highly inflexible and have high volume/low variety products. This nature of the textile industry makes implementing lean manufacturing techniques a challenge; hence implementing lean techniques in a textile industry has been taken up as a challenge. We have chosen a combination of value stream mapping (VSM), 5S, kanban, kaizen, poka-yoke, and visual controls to improve the processes. The achievement potential scores before and after lean implementation has been highlighted using radar diagrams. The findings of this study reveal that a thorough analysis of the process, setup, and changeover time (CO), use of colour coding for identification of volume-mix, use of kaizen and quality circles which empower the workforce, are some of the various keys to a successful lean implementation in a textile industry.